IHDĀD MASA BERKABUNG DALAM TINJAUAN PARA MUFASSIR DAN FUQAHA - Muhammad Faisol (Hukum Islam, 2017)
Islamic sharia comes not only to realize the humankind benefits in the world and the hereafter but also to realize the profit (maslahah) and to prevent the damage. Islamic sharia is essentially a virtue. Islam sharia is very concerned about social problems. In practice, it protects 5 things including religion, soul, intellect, descent, and property. Islamic Sharia also gives priority to women with great attention in which Islam frees women from the shackles of ignorance (jahiliyah) and saves them from the tyranny that occurred at that time mainly related to marriage and divorce and their impacts. One of the rules is the law of marriage for the woman whose husband passed away known as the law of ihdad or haddad. In this law, a woman must have a period of mourning after the death of her husband followed the iddah period. The mufassir (al Quran interpreter) and Fuqoha (Islamic jurist) agree that the period of iddah for women is to preserve the glory of women, guard their souls and their rights. Maintaining the rights of morality and humanity is aimed to realize the profit (maslahat) of religion and the world for women. A woman during iddah period in her husband's house is a tribute to her former husband and shows a sense of grief and respect for the family's feelings because of the sanctity of family relationships. Therefore women should spend their iddah at home except in an emergency situation.جاءت الشريعة الإسلامية لتحقيق مصالح العباد في الدنيا والآخرة كما جاءت لجلب المصالح ودرء المفاسد . فالشريعة الإسلامية في جلها خير.وقد اهتمت الشريعة بكل قضايا المجتمع وعلى رأسها الإنسان وقضت بالمحافظة على الكليات والضروريات الخمس الدين والنفس والعقل والنسل والمال.وأولت الشريعة الإسلامية المرأة اهتماماً عظيماً فحررتها من قيود الجاهلية وأنقذتها من الظلم الواقع عليها في مجالات الحياة ومن ضمن هذه الأشياء ما يتعلق بزواجها وطلاقها وما يترتب على ذلك من آثار ، ومن الآثار التي عالجتها الشريعة الإسلامية في زواج المرأة هي حالة وفاة زوجها وما ينتج عنه من أحكام مثل الإحداد أو الحداد يعني التزام المرأة المتوفى عنها زوجها مظاهر الحزن والأسى على زوجها طيلة مدة العدة.        اتفقت كلمة  المفسرين و الفقهاء أن عدة المرأة المتوفى عنها زوجها إنما هي حفظ لكرامتها وصون لنفسها وحفظ لحقوقها ورعاية لقيم أخلاقية وإنسانية تهدف في جملتها إلى تحقيق مصالح دينية ودنيوية للمرأة.اعتداد المرأة في بيت الزوجية فيه تعظيم لحق الزوج وإظهار الحزن عليه ومواساة لأهله وبيان لقدسية العلاقة الزوجية فلا تعتد في غير بيت الزوجية إلا للضرورة.Kata-Kata Kunci: Ihdād, Berkabung, Mufassir, Fuqaha